Kualitas Fisik Silase Rumput Gajah dan Ampas Tahu Segar dengan Penambahan Sirup Komersial Afkir: The Physical Quality of Elephant Grass and Fresh Tofu Dregs Silage with Rejected Commercial Syrup Addition - Sadarman; Dewi Febrina; Teguh Wahyono; Randi Mulianda; Novia Qomariyah; Rizki Amalia Nurfitriani; Fitrah Khairi; Danung Nur Adli Adli; Suci Desraini Romli; Zulkarnain; Agustin Bayu Prastyo (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
This study aimed to evaluate the addition of rejected commercial syrup on the physical quality of silage made from elephant grass and fresh tofu dregs. The making process and harvesting of silage were conducted out at the Laboratory of Nutrition and Feed Technology, Faculty of Agriculture and Animal Husbandry, UIN Suska Riau. The ingredients used were elephant grass, fresh tofu dregs, and commercial syrup. Completely Randomized Design (CRD) consisting of 3 treatments and 7 replications was used in this study. The treatments in this study were P1: elephant grass + fresh tofu dregs, P2: P1 + 5% commercial syrup, and P3: P1 + 10% commercial syrup. Variable observed were dry matter loss, temperature, pH, color, texture, aroma, and fungal growth. The data obtained were analyzed based on analysis of variance, and if there was a significant effect between treatments, then it was followed by Duncan's test at 5% level. The results of this study that the addition of rejected commercial syrup had a significant effect (p<0.05) on dry matter loss, pH, color, texture, and aroma, while temperature and fungal growth were not significant. Silage dry matter loss was in the range of 5.83%-7.61%, silage temperature under normal conditions was 28.7°C -29.6°C, silage pH was within normal limits of 3.61-3.95, silage color followed the color of the commercial syrup used, the aroma was typical of silage to fresh, the texture of the silage was medium to fine, and was not overgrown with fungus. Increasing the level of addition of rejected commercial syrup showed a decrease in the pH value and dry matter loss was better than the control. Based on the results of this study, it could be concluded that the addition of commercial syrup at the level of 10% BK could improve the physical characteristics of silage made from elephant grass and fresh tofu dregs which were stored for 30 days. Key words: elephant grass, silage, syrup, tofu dregs